Chemical composition, antimicrobial, and antioxidant potential of the essential oil from aerial parts of Cleome rostrata Bobrov, a novel study - Joukar, Manijeh; Larijani, Kambiz; Farjam, Mohammad Hossein; Givianrad, Mohammad Hadi; Nematollahi, Fereshteh (2023)
This study aimed to identify the chemical compounds present in the essential oil of Cleome rostrata for the first time. C. rostrata belongs to the Cleome genus of the Cleomaceae family. The study was conducted to investigate the phytochemical composition, antimicrobial activity, and antioxidant potential of the aerial parts of C. rostrata. GC-MS analysis identified a total of 39 compounds. The major components of C. rostrata aerial parts were found to be farnesan (10.49%), 4-methyl-dodecan-1-ol (14.07%), 2,7-dimethylnaphthalene (4.81%), phytane (6.05%), and tetradecane, 4-methyl- (4.81%). The methanol extract of the plant was evaluated for its total flavonoid content using the aluminum chloride colorimetric method. The methanol extract of C. rostrata exhibited high total flavonoid content, measuring 18.04 mg/g extract. The methanolic extract also exhibited significant antimicrobial activity against three fungal strains and three Gram-positive bacterial strains. Notably, the highest activity was observed against Aspergillus niger at a concentration of 16 mg/mL. Moreover, the extract demonstrated potent antioxidant activity, as evidenced by its IC50 value of 202.48 μg/L in the DPPH test. These findings highlight the potential of C. rostrata as a source of natural antioxidants and antimicrobial agents with potential applications in food preservation and pharmaceuticals.
Keywords: Essential oils; Medicinal plants